Sildenafil use in patients with olanzapine-induced erectile dysfunction - Atmaca, M; Kuloglu, M; Tezcan, E (Springernature, 2002)
In the present study, we aimed to examine the efficacy of sildenafil in patients with an antipsychotic (olanzapine)-induced erectile dysfunction (ED). The study group comprised 10 patients who experienced ED associated with the use of olanzapine. The patients initially received 50 mg sildenafil at baseline. If clinically indicated, titration up to 100 mg was permitted. All patients were assessed by Clinical Global Impression-Improvement (CGI-I) and International Index of Erectile Dysfunction (IIEF) scales at baseline and weeks 2 and 4. At final assessment, three patients were considered 'very much improved' and four 'much improved' according to CGI-I. Our results suggest that sildenafil use is effective and well-tolerated in patients with olanzapine-induced ED.
Keywords: olanzapine; haloperidol; sildenafil; antipsychotic